Dental Arch Changes Concurred Wıth Bonded Rapıd Maxıllary Expansıon - Sevil Akkaya; Sumru Hızlan Lorenzon (Galenos Yayinevi, 1996)
The aim of this study was to evaluate dental arch and arch perimeter changes using bonded rapid maxillary expansion. The material consisted of orthodontic casts which were taken from 5 girls, 7 boys 12 patients at the beginning of treatment, at the end of treatment and at the end of retention period. At the beginning of treatment, the average chronological ages were 11.96 years. The treatment time varied from 0.70-1.60 months. At the end of active treatment same appiances were worn for retentive purposes for an additional 3 months. When the findings are evaluated throughout the reseacrh period; increases in the tranversal width between the upper first molars, upper first premolars, upper canines, lower first molars, lower canines and in the upper arch perimeter were obtained.